Memória háptica e visual em idosos: Avaliação experimental por meio de tarefas de recordação e reconhecimento - Gadelha, Maria José Nunes (2016)
Memory is a multiple system constituted by processes of codification, storage, and recollection of information. Haptic memory refers to the acquisition of information through the active manipulation of objects. Only a few studies were found comparing long term forgetting of haptic and visual memory in healthy older adults. Therefore, this research aimed at evaluating the rates of forgetting of information processed through the haptic modality in comparison with the visual, after different time intervals, and through tasks of free recall and recognition, in a sample of 144 older adults, of both genders, with no cognitive impairment, who were able to read and write. For that, a wooden box was used specifically for the presentation of the haptic stimuli, and a rotating platform was used for the presentation of the visual stimuli. The procedure consisted in two phases, one of studying (presentation of the stimuli), and one of testing (tasks of free recall or recognition), conducted immediately after time intervals of 20 or 30 minutes. A two-way ANOVA for the free recall task showed significant main effects of accuracy (Pr) between the conditions haptic and visual, and between the evaluated time intervals, [F(1,66) = 9.9, p = .002, ?p² = .13] e [F(2,66) = 3.19, p = .047, ?p² = .088], respectively. Post hoc contrasts using Bonferroni correction revealed significant differences between the Pr in the haptic and in the visual conditions after the intervals of 20 and 30 minutes, in which the older adults presented a Pr of 10.5% and 9%, larger for the visual condition than the haptic condition, respectively. Regarding the two-way ANOVA for the recognition task, there were no significant main effects between Pr in the haptic and visual conditions, nor in the evaluated time intervals. These results showed that for free recall tasks there might be an advantaged in the retention of visual rather than haptic stimuli, and for recognition tasks the type of stimulus does not interfere in the final retention, suggesting that memory alterations suffered by older adults might be related to the type of sensorial modality used in the codification of stimuli and to the type of recollection task being used.